Analisis Kinerja Rantai Pasok Perum BULOG Menggunakan Model SCOR dan AHP: Studi Kasus pada Perum BULOG Kantor Cabang Subang - Anis Rusyda Maliana; Alim Setiawan Slamet; Dhani Satria Wibawa (Perum BULOG, 2026)
Background: The institutional transformation of Perum BULOG from a Non-Departmental Government Agency into a Public Corporation under The State-Owned Enterprises has transformed its strategic orientation from a dominant Public Service Obligation (PSO) role toward commercial activities. Differences in financing schemes, distribution mechanisms, and operational regulations between Government Rice Reserves (Cadangan Beras Pemerintah/CBP) and commercial rice require a systematic assessment of their supply chain performance.Objectives: This study evaluated the supply chain performance of CBP and commercial rice at the Subang Branch Office of Perum BULOG.Methods: This study uses a qualitative method that analyzes the CBP and commercial rice supply chains at Perum BULOG Subang Branch Office as the research locus. Primary data were collected from December 2024 to June 2025 through observation, in-depth interviews, and questionnaires to five expert informants selected by purposive sampling. The unit of analysis focused on the company's internal performance by integrating the Supply Chain Operations Reference (SCOR) model for attribute measurement and the Analytic Hierarchy Process (AHP) for indicator priority weighting.Results: The findings indicated that CBP rice achieved a supply chain performance score of 84.25%, classified as good, whereas commercial rice attained a score of 62.31%, reflecting moderate performance. AHP results highlight strengths in operational flexibility, warehouse infrastructure, and storage capacity, while also identifying the need to strengthen ERP-based analytical capabilities for more effective operational planning.Conclusion: The CBP rice supply chain performance has demonstrated superior performance compared to commercial rice, with agility and reliability as dominant attributes. However, asset efficiency and sustainability remain important. Optimizing planning, asset utilization, and information technology are key areas for supply chain performance improvement